Integrating English Language and History Learning Through Visual Arts at Primary School - Musdalifah, Musdalifah (ETDC: Indonesian Journal of Research and Educational Review, 2025)
Learning world history in English using an international curriculum (Pearson Edexcel) poses difficulties for elementary school students. At Makassar Independent School (MIS), innovative learning methods are needed to help students understand complex historical material while keeping it engaging and accessible. This study intends to describe the role of creative arts, particularly drawing, as a pedagogical approach in teaching history in English. This study used a descriptive qualitative method. The subjects involved students in grades 2, 4, and 5 in history at Makassar Independent School. Data was collected through classroom observations to see how arts integration was carried out in the learning process. The research findings indicate that teachers have implemented a combination of learning methods, such as inquiry-based learning, discussion, and interactive learning. Drawing served as the final medium of articulation through which students visually expressed their profound understanding of historical topics. Through drawing activities, students were more enthusiastic and able to absorb the subject matter more effectively even though the medium of instruction was English. This study contributes to interdisciplinary learning strategies (arts and history). The results confirm that fine arts can be used as a cognitive tool to validate students' understanding in collaborative schools while also serving as a reference for educators in creating more inclusive and creative history classes.